Case report: Two cases of Poirier-Bienvenu neurodevelopmental syndrome and review of literature - Chen, Xiaolan; Han, Yunli; Li, Xing; Huang, Shiqin; Yuan, Hai; Qin, Yuanhan (Frontiers in Pediatrics, 2023)
The Poirier-Bienvenu neurodevelopmental syndrome (POBINDS) is a rare disease caused by mutations in the CSNK2B gene, which is characterized by intellectual disability and early-onset epilepsy. Mosaicism has not been previously reported in CSNK2B gene. POBINDS is autosomal dominant and almost all reported cases were de novo variants. Here, we report two patients were diagnosed with POBINDS. Using Whole Exome Sequencing (WES), we detected two novel CSNK2B variants in the two unrelated individuals: c.634_635del (p.Lys212AspfsTer33) and c.142C>T (p.Gln48Ter) respectively. Both of them showed mild developmental delay with early-onset and clustered seizures. The patient with c.634_635del(p.Lys212AspfsTer33) variant was mutant mosaicism, and the proportion of alleles in peripheral blood DNA was 28%. Further, the literature of patients with a de novo mutation of the CSNK2B gene was reviewed, particularly seizure semiology and genotype-phenotype correlations.